„... was man in Dresden schauet,/ Und was AUGUST vollführt und bauet,/ Sieht man sonst nirgends auf der Welt“ Drážďany a Varšava v strategiích reprezentace moci Augusta Silného za velké severní války - Iveta Coufalová (Theatrum Historiae)
The relation of August the Strong (1670−1733), Elector of Saxony and King of Poland, to Dresden and Warsaw and comparing his approach to these centres of Saxony-Poland during the Great Nothern War (1699/1700−1721) are realy thought-provoking topics. From the point of view of architectonical changes (primarily the Dresden Residence and the Royal Palace and Saxon Palace inWarsaw) of both towns and also material culture (f. e. decoration) it is an attractive motif and the comparision breeds till unheeded questions reflecting August the Strong and representation of his power. The following text focuses on the relation of this Elector/King to the space of the town residences and also on the possibilities of „disciplination of the town space“ during the war.